But Who Will Get Billy? The Effect of Child Custody Laws on Marriage - Elaina Rose; Crystal (Ho Po) Wong (Institute for the Study of Labor (IZA), 2014)
Under the tender years doctrine in effect until the 1970's, custody was virtually always awarded to the mother upon divorce. Gender-neutral custody laws introduced beginning in the 1970's provided married fathers, in principle, equal rights to custody. Subsequent marriage-neutral laws extended the rights to unmarried fathers. We develop a theoretical model of the effect of custody regime on marriage and test the model's predictions using a unique data set that merges custody law data with data from the Current Population Survey and Vital Statistics. We find that, under marriage non-neutrality, the introduction of gender-neutral laws reduced the hazard into marriage by at least 7.9 percent. There is no evidence that moving from marriage non-neutrality to marriage neutrality affected marriage under the gender-neutral custody regime.
Keywords: J1; J12; J16; J18; K36; 330; marriage; custody; family law